Factor Analysis of investment intention: Millennials and Gen Z perspective - Wan Suryani; Fitriani Tobing; Yesika Emelia Girsang (Jurnal Inovasi Ekonomi, 2022)
This study aims to determine what factors influence the investment interest of millennials (Y) and Z generations in North Sumatra. This research was conducted by survey method, and the number of respondents in this study was 280. The results indicate that two main factors determine millennials and generation z in investing intention: first, knowledge, self-motivation, social environment that has investment experience, and initial capital; and second, variables include information, transparency, social media influencers, and financial literacy.